Estudio de los parámetros tecnológicos para la industrialización del cacao a fin de obtener productos cosméticos (tinte para cabello). - Triviño Guillen, Jennifer Viviana (2017)
Considering the need to have an industrialized process, which allows the diversification of cocoa almond application, this study aims at obtaining hair dye based on this berry, which allows analyzing variables implicit in maintaining the properties of cocoa in The dye, considering that the methods by solvents or by high temperatures could alter the quality of the product. This study consisted in evaluating two methods of drying with low temperatures and standardized to avoid altering the properties of cocoa, two varieties of cocoa: National and CCN51 and two additional additives: sage leaf and coffee. The dye extraction was started by obtaining the almond, which was dried: solar and in an electric stove with a temperature of 60 ° C, followed by roasting of the cocoa and peeling, then the grain was grinded and Separation of phases to extract the fat, analysis of the pH and acidity of each one of the samples at laboratory level was carried out. For the evaluation of the dyeing process, a completely randomized block statistical model with AxBxC factorial arrangement was applied with two replicates. The pH and acidity of the product were evaluated in this research. It was verified that any of the varieties can be used That did not report the method of dehydration and coffee as the natural dye were the best pH obtained, which allows to conclude that the research achieved positive deductions, the results obtained in this study could serve as a starting point in further research.